Signifikansi Desain Pembelajaran dalam Menunjang Kesuksesan Mengajar - Basri Basri (Nizham Jurnal Studi Keislaman, 2013)
Instructional design is a design study conducted in order to transfer knowledge effectively its occur between teacher and student. Instructional design should describe the knowledge to be understood by the students, the learning objectives to be achieved by designing methods, strategies, and instructional media. Learning goals focused on student behavior or actions (performace) as a type of output that can be observed and indicate that the student had engaged in learning. The learning process can be managed, if the teacher has a view that is consistent with his philosophy, that the success of the teacher in teaching can be seen from the extent of the teacher in implementing lesson plans apply, so the indicators set out in the lesson plan is well absorbed by the students and can be measured through formative tests conducted teacher at the end of the lesson.